2010
DOI: 10.1097/jcp.0b013e3181ca03df
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of Multiple Measures of Adherence to Antipsychotic Medication in First-Episode Psychosis

Abstract: This study evaluates how much agreement there is between subjective reports of adherence to antipsychotic medication and objective or derived measures of adherence in first-episode psychosis (FEP) and asks if any adherence measure could approximate a gold standard based on correlation to symptom improvement in the early phase of treatment. Adherence was assessed in 81 FEP subjects on a monthly basis by reports from patients, clinicians, family, and pill counting. A consensus measure of adherence was derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…Par ailleurs, la non-observance thĂ©rapeutique s'inscrit plutĂŽt dans un continuum que dans une binaritĂ© de type tout ou rien. Il n'existe pas de mĂ©thode standard et fiable en pratique courante pour l'Ă©valuation de l'observance thĂ©rapeutique et par consĂ©quent, il est difficile d'obtenir une Ă©valuation vraiment exacte de celle-ci [5][6][7][8] . Toutefois, un consensus d'experts conclut sur l'importance d'utiliser plusieurs mĂ©thodes d'Ă©valuation Ă  la fois pour mesurer l'observance 9 .…”
Section: Observer La Non-observanceunclassified
“…Par ailleurs, la non-observance thĂ©rapeutique s'inscrit plutĂŽt dans un continuum que dans une binaritĂ© de type tout ou rien. Il n'existe pas de mĂ©thode standard et fiable en pratique courante pour l'Ă©valuation de l'observance thĂ©rapeutique et par consĂ©quent, il est difficile d'obtenir une Ă©valuation vraiment exacte de celle-ci [5][6][7][8] . Toutefois, un consensus d'experts conclut sur l'importance d'utiliser plusieurs mĂ©thodes d'Ă©valuation Ă  la fois pour mesurer l'observance 9 .…”
Section: Observer La Non-observanceunclassified
“…1Y3 Specifically in firstepisode psychosis (FEP), improved adherence to antipsychotic pharmacotherapy during the early course of treatment was shown to improve the short-term clinical outcome of patients with psychotic disorders. 4 In our previous study, 5 we reported that 20% to 56% nonadherence to medication in FEP and that nonadherence was highly correlated to a poorer clinical outcome. The link between poor adherence and poor outcome has been clearly established.…”
mentioning
confidence: 97%
“…84 and similar predictive validity. 11 Individuals' adherence fluctuates: one group 12 found 33%-44% were nonadherent sometime in any 6-month period and 53% sometime in the first 2 years, while another 13 found 63% nonadherent for at least a week over a year. Another study 14 estimated 45% took under 75% of antipsychotics in the first 6 months, while 42%-60% were rated as nonadherent at some point in first episode psychosis cohorts followed up for at least 1 year, 12,13,[15][16][17] particularly if the samples were juvenile or all had schizophrenia.…”
Section: What Is the Prevalence And Impact Of Poor Adherence After Fimentioning
confidence: 99%